Pengaruh Kepuasan Kerja dan Hubungan Atasan-Bawahan terhadap Stres Kerja Karyawan PT Central Mega Kencana - Cindy Putri; Abdul Haris; Nefi Darmayanti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This research aims to determine the influence of job satisfaction and leader-member exchange on job stress employee of PT Central Mega Kencana. This research was conducted in February 2022. This study used a quantitative method in which the sampling technique was through a non-probability sampling technique using simple random sampling where the subjects in this study amounted to 100 people. Data were collected using was a Likert scale consisting of three scales, namely the job satisfaction scale, leader-member exchange scale, and work stress scale. The data analysis technique used multiple regression analysis. The results showed that there was a significant positive effect between job satisfaction and leader-member exchange on the work stress of employee of PT Central Mega Kencana. This is indicated by the coefficient F reg = 18,852 with p < 0.05, and the coefficient R = 0,529 with p < 0.05 and R2 = 0,280. The total contribution of these two variables was 28%, while the remaining was 72% is influenced by other factors on job stress. From the result of the study, it can be concluded that job satisfaction and leader-member exchange jointly affect the work stress of employee of PT Central Mega Kencana.